NEGOTIATION BETWEEN STAKEHOLDERS OF COMMODIFICATION: Roles and Impacts as Stakeholders in Tebing Breksi Prambanan - Bayu Pamungkas; Warto Warto; Mugijatna Mugijatna (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2019)
Commodification practice always deals with 3 parties, which our society, government, and private institution. Considered as cultural preservation, Tebing Breksi becomes an object of commodification in Sambirejo Prambanan since 2014. Its commodification arises several conflicts among its stakeholders due to each stakeholder has their own importance and interest. Compared to other commodification practices, bottom-up tourism management is applied that making the commodification of Tebing Breksi differs to others. This research is remarkable dealing with its findings that differenciate the commodification practice between society and government or private institution. This research aims to find the implication of commodification for tourism field using bottom-up tourism management. Whereas, the main purpose of this research is to describe the negotiation between stakeholders of commodification in Tebing Breksi. The method of this research is ethnography by applying in-depth reporting. The findings of this research prove that negotiation between stakeholders of commodification is the impact of a different way of thinking as well as the group’s interest in each stakeholder. Nevertheless, the changes happen among society in Tebing Breksi confirmed Tebing Breksi as an alternative tourism attraction in Prambanan.